Chapter Per Sergio Caruso - Sciarra, Silvana (Studi e saggi, 2023)
In a short message that testifies to a long and solid relationship of friendship, reference is made to the vast multidisciplinary culture of Sergio Caruso, to highlight his propensity to listen and constantly discover new landings, both in scientific research and in the activity of therapist.